2000
DOI: 10.3171/jns.2000.93.supplement_3.0152
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery using 90 Gy for trigeminal neuralgia

Abstract: Object. The purpose of this paper was to assess the treatment of trigeminal neuralgia (TN) with the higher than normal dose of 90 Gy. Methods. Forty-two patients with typical TN were treated over a 3-year period with gamma knife radiosurgery. Every patient received a maximum dose of 90 Gy in a single 4-mm isocenter targeted to the root entry zone of the trigeminal nerve. Thirty of 42 patients had undergone no prior treatments. The median follow-up period was 14 months (range 2–30 months). Thirty-one patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(49 citation statements)
references
References 8 publications
2
45
1
Order By: Relevance
“…In patients with essential TN, more than 88% of patients attained significant relief, similar to prior reports on gamma knife radiosurgery (9,11,(19)(20)(21)23). Prior treatment was the primary factor associated with poor results.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In patients with essential TN, more than 88% of patients attained significant relief, similar to prior reports on gamma knife radiosurgery (9,11,(19)(20)(21)23). Prior treatment was the primary factor associated with poor results.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we found a trend toward increased numbness with increased dose. However, as in other reports, the majority of patients described their change in facial sensation as an intermittent tingling or limited and minor hypesthesia (20,30).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Since the first multi-institutional study by Kondziolka et al (22) suggested a standard method and dose-selection guidelines for radiosurgery for TN, many studies have investigated the safety and efficacy of radiosurgery for TN (12,(14)(15)(16)(17)(18)(19)(20)(21). These data have demonstrated that radiosurgery is a safe technique for the management of TN, because trigeminal sensory disturbance, the main complication of radiosurgery for TN, only developed in approximately 10% of the patients (10), and the rate of immediate pain relief seemed to be comparable to those of other surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, elderly patients with TN and concurrent medical illness can avoid the mortality and morbidity risks associated with surgical interventions by undergoing radiosurgery. In addition, radiosurgery has been reported to provide successful initial pain relief at a rate of 80-90%, usually within 6-12 months after radiosurgery, and this rate is comparable to the rates of other treatments (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, few reports have been published concerning the longterm outcomes after radiosurgery for TN, and few studies have investigated the prognostic factors of clinical outcome after radiosurgery for TN (11,13).…”
Section: Introductionmentioning
confidence: 88%